The ventral peptidergic system of the adult ascidian Ciona robusta (Ciona intestinalis Type A) insights from a transgenic animal model - Osugi, Tomohiro (Sci Rep, 2020)
Ascidians are the sister group of vertebrates and occupy a critical position in explorations of the evolution of the endocrine and nervous systems of chordates. Here, we describe the complete ventral peptidergic system in adult transgenic Ciona robusta (Ciona intestinalis Type A) which expresses the Kaede reporter gene driven by the prohormone convertase 2 (PC2) gene promoter. Numerous PC2 promoter-driven fluorescent (Kaede-positive) non-neural cells were distributed in the blood sinus located at the anterior end of the pharynx, suggesting the acquisition of a peptidergic circulatory system in Ciona. Kaede-positive ciliated columnar cells, rounded cells, and tall ciliated cells were observed in the alimentary organs, including the endostyle, pharynx, esophagus, stomach, and intestine, suggesting that digestive functions are regulated by multiple peptidergic systems. In the heart, Kaede-positive neurons were located in the ring-shaped plexus at both ends of the myocardium. Nerve fiber–like tracts ran along the raphe and appeared to be connected with the plexuses. Such unique structures suggest a role for the peptidergic system in cardiac function. Collectively, the present anatomic analysis revealed the major framework of the ventral peptidergic system of adult Ciona, which could facilitate investigations of peptidergic regulation of the pharynx, endostyle, alimentary tissues, and heart.